Development of a Virtual Simulator for Planning Mandible Osteotomies in Orthognathic Surgeries - Govea-Valladares, Eder H; Govea-Valladares, Eder H; Medellín-Castillo, H I; Lim, T; Khambay, B; Ballesteros, J (Revista Mexicana de Ingenieria Biomedica, 2012)
Surgery knowledge and training is typically transmitted by the teacher-student method. In particular, the training process is carried out during real surgical interventions and under supervision of an experienced surgeon. Recent advancements in computer interaction technology and virtual environments allow a wide variety of surgical procedures to be simulated. Virtual reality (VR) applications range from art to engineering, science and medicine. In medicine, virtual simulators are being developed for pre-operative planning and training purposes. In this way, the transferring process of surgery knowledge and training can be enhanced and speed up. Medical VR simulators are characterized by their large demands on visual and physical behavior, and more recently the demand for the sense of touch, which is an essential aspect in surgery. Regarding the maxillofacial surgery, one of the most common surgical procedures is the "Bilateral Sagittal Split Ramus Osteotomy Mandibular" (BSSROM), which is used to relocate the jaw at the correct position, fix jaw deformities, get better functionality of the jaw and improve the patient aesthetic. In this paper the development of a 3D virtual simulator for planning mandible osteotomies in orthognathic surgeries is presented; in particular the work is focused on the BSSROM procedure. The proposed system has been developed in an open-source platform that provides a high level of realism and interaction, and where the surgeons are able to cut bone in a 3D free-form way; thus enhancing the traditional virtual osteotomy approach which is based on cutting planes. Some of the main functionalities of the system include: virtual reality environment and real-time response; 3D visualization of anatomical models and tools; free-form manipulation and interaction of cutting tool, bone, and bone fragments; simulation of single and multiple osteotomies; cutting planes osteotomies and free-form cut osteotomies. The description, development and implementation of the system are presented in this paper. The results have shown that the proposed system is practical and can be used for planning and training mandible osteotomies.